PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 10 BENGKALIS - Nurainingsih Nurainingsih; Lazim Lazim; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to improve science learning outcomes fifth grade students of SD Negeri 10 Bengkalis by applying Cooperative Learning Model Two Stay Two Stray (TSTS). Subjects in this study were students of class V with the number of 20 people. Instrument of data collection in this research is the observation and learning outcomes test. The research concluded the implementation of this learning model can increase the activity of teaching and student and learning outcomes. At the first meeting of the first cycle, teacher activity categorized simply by percentage of 58.33%. At the second meeting, becomes 70.83% to its category to be good. In the second cycle, the first meeting, the teachers’s activities percentage to 83.33% in its category to be very good. The second meeting was also categorized very well with a percentage of 95.83%. Activities of students at the first meeting of the first cycle categorized enough with the percentage of 58.33%. At the second meeting, the percentage be 66.67%, and categorizing them well. At the first meeting of the second cycle, student activities can be categorized very well with a percentage of 83.33%. The second meeting become 91.67% with the very good category. Before action is taken, the average science student learning outcomes at 62.75. In the first cycle, the average student learning outcomes increased to 70.25. That is, an increase amounted to 11.95%. In the second cycle, the average student learning outcomes increased to 75.93. That is, an increase amounted to 29.48%.Keyword: Cooperative Learning Model Two Stay Two Stray (TSTS), science learning outcomes.